Surface treatment method of O3 type nickel-based sodium ion battery positive electrode material, positive electrode material and battery

By performing organic acid treatment and sintering on the positive electrode material of O3 type nickel-based sodium ion battery, a dense coating layer is generated, which solves the problems of phase change, environmental sensitivity and kinetic slowness of sodium ion battery materials, and achieves high cycle stability and improve rate performance, suitable for large-scale production and maintain high stability and high energy density in the air.

CN119133354APending Publication Date: 2024-12-13YULIN YUSHEN IND ZONE ENERGY TECH DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411283191.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode materials have phase transition problems, environmental sensitivity and slow kinetics during charging and discharging, which affect the long-term stability and practical application of the battery.

Method used

The positive electrode material of O3 type nickel-based sodium ion battery is treated with organic acid to generate a dense cladding layer, stabilize the lattice structure, enhance the Na+ transmission dynamics, and improve the cyclic stability and rate performance of the material through sintering treatment.

Benefits of technology

It significantly improves the cyclic stability and rate performance of the material, reduces costs, is suitable for large-scale production, and maintains high stability and high energy density in the air.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005042301170000011
    Figure HDA0005042301170000011
  • Figure HDA0005042301170000012
    Figure HDA0005042301170000012
  • Figure HDA0005042301170000021
    Figure HDA0005042301170000021
Patent Text Reader

Abstract

The invention relates to a surface treatment method of an O3-type nickel-based sodium ion battery positive electrode material, a positive electrode material and a battery, the O3-type nickel-based sodium ion battery positive electrode material is placed in an organic acid for reaction, then sintering treatment is performed, and the positive electrode material after surface treatment is obtained; the chemical general formula of the O3 type nickel-based sodium ion battery positive electrode material is Naa [NibMncMed] O2 + e, and Me is one or a combination of more of transition metals Ni, Fe, Mn, Co, Ti and Cr; a, b, c, d and e respectively correspond to the molar ratio percentages of the elements; a is larger than or equal to 0.8 and smaller than or equal to 1, b is larger than or equal to 0.3 and smaller than or equal to 0.9, and c is larger than or equal to 0 and smaller than or equal to 0.5, 0lt; d < = 0.33,-0.02 < = e < = 0.02; the organic acid is at least one of benzoic acid, acetic acid, citric acid, decanoic acid and tartaric acid; the O3 type nickel-based sodium-ion battery positive electrode material with a stable surface structure can be obtained on the basis that the electrochemical performance of the material is not affected, the battery positive electrode material treated in the manner can be applied to batteries, and the cycling stability and the rate capability are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of positive electrode materials for sodium ion batteries, and in particular to a surface treatment method for positive electrode materials for O3 type nickel-based sodium ion batteries, positive electrode materials and batteries. Background Art

[0002] At present, with the explosive growth of the lithium-ion battery market, the consumption and demand for lithium resources are also rising year by year. However, the abundance of lithium in the earth's crust is only 17 parts per million. Sodium is the sixth most abundant element and the fourth most abundant metal element in the earth's crust, with an abundance of more than 1,300 times that of lithium, and sodium resources are widely distributed. At present, the technology for making sodium chloride from seawater is very convenient and efficient, and the industry for purifying sodium salts from seawater is well developed. In addition, sodium-ion batteries and lithium-ion batteries have similarities in reversible storage and migration mechanisms. Therefore, sodium-ion batteries have attracted much attention and are an important supplement and strategic reserve for lithium-ion batteries, which can ensure national energy security.

[0003] At present, the research hotspots of positive electrode materials for sodium ion batteries mainly include transition metal oxides, polyanion compounds and Prussian blue compounds. Among them, the advantages of transition metal oxides as energy storage materials are very obvious, such as rich active element centers, high reversible specific capacity and good electrochemical activity. They are a very promising type of material in the history of research on positive electrode materials for sodium ion batteries. However, during the charging and discharging process, transition metal oxides will face a series of problems: First, both the P2 phase and the O3 phase will have phase change problems, which is not conducive to the long-term and stable cycling of the battery. Second, another major challenge facing transition metal oxides is their environmental sensitivity, especially when exposed to air, they are easy to absorb moisture, which leads to poor battery performance and increases transportation costs. Third, due to the Na + The radius is large, so Na-containing transition metal oxides are usually kinetically slow. These are all factors that are not conducive to the long-term stable cycle of the battery, and also restrict its large-scale practical application. The patent application with application number CN202310551196.2 discloses a surface-modified sodium-ion battery positive electrode material and its preparation method and application. The surface-modified sodium-ion battery positive electrode material uses a conventional sodium-ion battery positive electrode material as the core, and a layer of organic fluorine polymer is wrapped on its surface; the material's affinity for water is reduced to achieve better hydrophobic properties of the material. This method is costly and has a complicated processing flow. Therefore, it is particularly important to seek a surface treatment method for sodium-ion battery positive electrode materials with simple process and low equipment requirements. Summary of the invention

[0004] In order to overcome the problems existing in the above-mentioned prior art, the purpose of the present invention is to provide a surface treatment method for an O3 type nickel-based sodium ion battery positive electrode material, a positive electrode material and a battery, which mainly designs and adjusts the positive electrode material of the sodium ion battery through surface treatment, and further improves the influence of changes in factors such as atoms / electrons, chemical components, crystal structure, electrode interface, etc. on the battery capacity, rate performance and cycle stability, and has the characteristics of simple preparation process, low equipment requirements and excellent performance of the synthesized product.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] A surface treatment method for an O3 type nickel-based sodium ion battery positive electrode material, comprising placing the O3 type nickel-based sodium ion battery positive electrode material in an organic acid for reaction, and then sintering the positive electrode material to obtain a surface-treated positive electrode material;

[0007] The O3 type nickel-based sodium ion battery positive electrode material has a chemical formula of Na a [Ni b Mn c Me d ]O 2+e , wherein Me is a combination of one or more transition metals Ni, Fe, Mn, Co, Ti, Cr; a, b, c, d, e correspond to the molar percentages of the elements respectively; the relationship satisfies b+c+d=1, wherein 0.8≤a≤1, 0.3≤b≤0.9, 0≤c≤0.5, 0 <d≤0.33,-0.02≤e≤0.02;

[0008] The organic acid is at least one of benzoic acid, acetic acid, citric acid, capric acid and tartaric acid.

[0009] The placing in organic acid, one specific scheme is: placing the O3 type nickel-based sodium ion battery positive electrode material in organic acid vapor, drying, and then sintering to obtain the surface treated positive electrode material.

[0010] The evaporation temperature of the organic acid is 100 to 1000° C., and the time of being placed in the organic acid vapor is 0.25 to 2 hours;

[0011] The drying temperature is 60-150° C. and the drying time is 6-24 hours;

[0012] The drying method is spray drying, blast drying or vacuum drying;

[0013] The sintering treatment is carried out in an atmosphere of air or oxygen, with a heating rate of 2 to 5°C / min, a sintering temperature of 850 to 1000°C, and a sintering time of 10 to 24 hours.

[0014] The method of placing the mixture in an organic acid is as follows:

[0015] The O3 type nickel-based sodium ion battery positive electrode material is immersed in an organic acid solution, filtered, washed, dried, and then sintered to obtain a surface-treated positive electrode material.

[0016] The organic acid solution is prepared by dissolving the organic acid in pure water or ethanol solvent with a volume concentration of 10%-15%;

[0017] The immersion time in the organic acid is 2-12 hours;

[0018] The washing liquid is a neutral washing liquid;

[0019] The drying method is spray drying, air drying or vacuum drying;

[0020] The drying temperature is 60-150° C. and the time is 6-24 hours.

[0021] The sintering treatment is carried out in an atmosphere of air or oxygen, with a heating rate of 2 to 5°C / min, a sintering temperature of 850 to 1000°C, and a sintering time of 10 to 24 hours.

[0022] The present invention also includes an O3 type nickel-based sodium ion battery positive electrode material, the surface of which is treated by the above-mentioned surface treatment method.

[0023] The present invention also includes a battery, including an O3 type nickel-based sodium ion battery positive electrode material obtained after being treated by the above surface treatment method.

[0024] Compared with the prior art, the present invention has the following advantages:

[0025] (1) The organic acid provided by the present invention can form a dense coating layer on the surface of the layered positive electrode material after reacting with the layered positive electrode material, thereby reducing a series of side reactions occurring at the electrode / electrolyte interface; at the same time, the strong bonding force between the layered positive electrode material and the coating layer stabilizes the lattice oxygen, inhibits the escape of oxygen, enhances the structural stability of the material, and significantly improves the cycle stability and rate performance of the material.

[0026] (2) The present invention uses organic acid to consume the surface residual alkali in the material, thereby enhancing the Na+ transmission kinetics, effectively inhibiting the blocking of Na+ diffusion and the repeated consumption of active Na+, so that the material has the characteristics of high air stability and high energy density.

[0027] In summary, the salient feature of the layered cathode material prepared by the present invention is that the organic acid is combined with the sodium electrode layered cathode material through a surface treatment method, and the synthesis route is simple, the cost is low, and it is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1This is the XRD diagram of the positive electrode material after surface treatment in Example 1-4.

[0029] Figure 2 This is the SEM image of Example 2.

[0030] Figure 3 This is the first charge and discharge curve of Example 1-4 at a 0.2C rate.

[0031] Figure 4 This is the cycle performance diagram of Examples 1-4 at 1C rate.

[0032] Figure 5 This is the air stability test performance diagram of Example 2. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the embodiments described are only part of the embodiments of the present invention, rather than the features of all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the protection scope of the present invention.

[0034] Example 1

[0035] A surface treatment method for an O3 type nickel-based sodium ion battery positive electrode material comprises the following steps:

[0036] 25g of citric acid was dissolved in pure water and placed in a test tube and heated at 800℃ to form steam. 1 / 3 Mn 1 / 3 Ti 1 / 3 ]O2 was placed in citric acid vapor for 1 hour, then placed in a blast drying oven for drying at 100°C for 6 hours, and then moved to a muffle furnace and sintered at 850°C for 12 hours at a temperature rise rate of 2°C / min, and then naturally cooled to room temperature in an air atmosphere throughout the process to obtain the surface-treated positive electrode material O3-Na[Ni 1 / 3 Mn 1 / 3 Ti 1 / 3 ]O2.

[0037] The positive electrode material obtained in Example 1 was used to form a CR2032 button cell for electrochemical evaluation. The positive electrode material, conductive agent and binder were mixed in a mass ratio of 7:2:1 to prepare a slurry, and then coated on an aluminum foil current collector with a certain thickness. The electrolyte used a 1M NaClO4 solution, in which the solvent was a mixture of EC:DMC=1:1Vol% and 5.0% FEC in a volume ratio. Na sheets were used as negative electrodes and glass fiber separators were assembled into button cells in a glove box filled with argon.

[0038] The electrochemical properties of the material were tested using a battery testing system at room temperature (25°C), with a test voltage range of 2.0 to 4.0V. The cycle performance test conditions were: 0.2C charge and discharge three times (battery activation), followed by a charge and discharge test at a 1C rate.

[0039] Reference Figure 1 , Figure 1 The XRD diagrams of the positive electrode materials after surface treatment of Examples 1-4 are shown, wherein Example 1 has good crystallinity and still maintains an O3 phase structure with a stable surface structure.

[0040] Reference Figure 2 , Figure 3 The first charge and discharge curves of Examples 1-4 at 0.2C, wherein the first discharge specific capacity of Example 1 at 0.2C is 112.69 mAh / g.

[0041] Reference Figure 4 , Figure 4 The cyclic performance diagram of Examples 1-4 at 1C, wherein the first and 100th discharge specific capacities of Example 1 at 1C are 106.67 mAh / g and 92.21 mAh / g, respectively, and the capacity retention rate is calculated to be 86.44%.

[0042] Example 2

[0043] A surface treatment method for an O3 type nickel-based sodium ion battery positive electrode material comprises the following steps:

[0044] 40g of benzoic acid was dissolved in pure water and placed in a test tube and heated at 250℃ to form steam. 1 / 3 Mn 1 / 3 Cr 1 / 3 ]O2 was placed in benzoic acid vapor for 1.5 hours, then placed in a blast drying oven for drying at 80°C for 12 hours, and then moved to a muffle furnace for sintering at 900°C for 15 hours at a temperature rise rate of 4°C / min, and then naturally cooled to room temperature in an air atmosphere throughout the process. The surface-treated positive electrode material O3-Na[Ni 1 / 3 Mn 1 / 3 Cr 1 / 3 ]O2.

[0045] The preparation and assembly of the battery are the same as those in Example 1.

[0046] The electrochemical properties of the material were tested using a battery testing system at room temperature (25°C), with a test voltage range of 2.0 to 4.0V. The cycle performance test conditions were: 0.2C charge and discharge three times (battery activation), followed by a charge and discharge test at a 1C rate.

[0047] Reference Figure 1 , Figure 1 The XRD diagrams of the positive electrode materials after surface treatment of Examples 1-4 are shown, among which Example 2 has good crystallinity and still maintains a stable O3 phase structure on the surface.

[0048] Reference Figure 2 , Figure 2 The SEM image of Example 2 is shown. It can be seen from the figure that there is a dense coating on the surface of the material.

[0049] Reference Figure 3 , Figure 3 The first charge and discharge curves of Examples 1-4 at 0.2C, wherein the first discharge specific capacity of Example 2 at 0.2C is 122.68 mAh / g.

[0050] Reference Figure 4 , Figure 4 The cyclic performance diagram of Examples 1-4 at 1C, wherein the first and 100th discharge specific capacities of Example 2 at 1C are 105.32 mAh / g and 100.49 mAh / g, respectively, and the capacity retention rate is calculated to be 95.41%.

[0051] like Figure 5 The air stability test performance diagram of Example 2 is shown, which is to place Example 2 in the air for 15 days and then conduct a charge and discharge test. It can be seen from the figure that after Example 2 is placed in the air for 15 days, its first discharge specific capacity at 0.2C is still 115.60mAh / g, reflecting the excellent performance of the surface treatment method of the present invention in resisting air erosion.

[0052] Example 3

[0053] A surface-treated O3 type nickel-based sodium ion battery positive electrode material and method thereof, comprising the following steps:

[0054] 20g of tartaric acid was dissolved in pure water to prepare a 10% volume concentration organic acid solution. 1 / 3 Mn 1 / 3 Co 1 / 3 ]O2 was immersed in the solution for 4 hours, then filtered, washed with neutral detergent, placed in a vacuum drying oven for drying at 100°C for 10 hours, and then moved to a muffle furnace and sintered at 950°C for 15 hours with a temperature rise rate of 3°C / min, and then naturally cooled to room temperature in an air atmosphere throughout the process. The surface-treated positive electrode material O3-Na[Ni 1 / 3 Mn 1 / 3 Co 1 / 3 ]O2.

[0055] The preparation and assembly of the battery are the same as those in Example 1.

[0056] The electrochemical properties of the material were tested using a battery testing system at room temperature (25°C), with a test voltage range of 2.0 to 4.0V. The cycle performance test conditions were: 0.2C charge and discharge three times (battery activation), followed by a charge and discharge test at a 1C rate.

[0057] Reference Figure 1 , Figure 1 1-4 are XRD diagrams of Examples 1-4, wherein Example 3 has good crystallinity and still maintains an O3 phase structure with a stable surface structure.

[0058] Reference Figure 3 , Figure 3 1 is the first charge and discharge curve of Examples 1-4 at 0.2C. It can be seen from the figure that the first discharge specific capacity of Example 3 at 0.2C is 118.11 mAh / g.

[0059] Reference Figure 4 , Figure 4 The cyclic performance diagram of Examples 1-4 at 1C, wherein the first and 100th discharge specific capacities of Example 3 at 1C are 111.57 mAh / g and 94.88 mAh / g, respectively, and the capacity retention rate is calculated to be 85.04%.

[0060] Example 4

[0061] A surface-treated O3 type nickel-based sodium ion battery positive electrode material and method thereof, comprising the following steps:

[0062] 30g of acetic acid was dissolved in pure water to prepare an organic acid solution with a volume concentration of 15%. 1 / 3 Mn 1 / 3 Fe 1 / 3 ]O2 was immersed in the solution for 6 hours, then filtered, washed with neutral detergent, placed in a vacuum drying oven for drying at 120°C for 8 hours, and then moved to a muffle furnace and sintered at 1000°C for 15 hours at a temperature rise rate of 5°C / min, and then naturally cooled to room temperature in an air atmosphere throughout the process. The surface-treated positive electrode material O3-Na[Ni 1 / 3 Mn 1 / 3 Fe 1 / 3 ]O2.

[0063] The preparation and assembly of the battery are the same as those in Example 1.

[0064] The electrochemical properties of the material were tested using a battery testing system at room temperature (25°C), with a test voltage range of 2.0 to 4.0V. The cycle performance test conditions were: 0.2C charge and discharge three times (battery activation), followed by a charge and discharge test at a 1C rate.

[0065] Reference Figure 1 , Figure 1 1-4 are XRD diagrams of Examples 1-4, wherein Example 4 has good crystallinity and still maintains an O3 phase structure with a stable surface structure.

[0066] Reference Figure 3 , Figure 3 The first charge and discharge curves of Examples 1-4 at 0.2C, wherein the first discharge specific capacity of Example 4 at 0.2C is 114.93 mAh / g.

[0067] Reference Figure 4 , Figure 4 : This is the cycle performance diagram of Examples 1-4 at 1C, wherein the first and 100th discharge specific capacities of Example 4 at 1C are 107.21 mAh / g and 91.98 mAh / g, respectively, and its capacity retention rate is calculated to be 85.79%.

[0068] The present invention also includes an O3 type nickel-based sodium ion battery positive electrode material, the surface of which is treated by the above-mentioned surface treatment method.

[0069] The present invention also includes a battery, including an O3 type nickel-based sodium ion battery positive electrode material obtained after being treated by the above surface treatment method.

[0070] The above description is not intended to limit the present invention, and the present invention is not limited to the above examples. Any changes, modifications, additions or substitutions made by a person skilled in the art within the spirit and scope of the present invention shall also fall within the protection scope of the present invention.

Claims

1. A surface treatment method for an O3 type nickel-based sodium ion battery positive electrode material, characterized in that: The positive electrode material of the O3 type nickel-based sodium ion battery is placed in an organic acid for reaction, and then sintered to obtain a positive electrode material after surface treatment; The O3 type nickel-based sodium ion battery positive electrode material has a chemical formula of Na a [Ni b Mn c Me d ]O 2+e , wherein Me is a combination of one or more transition metals Ni, Fe, Mn, Co, Ti, Cr; a, b, c, d, e correspond to the molar percentages of the elements respectively; the relationship satisfies b+c+d=1, wherein 0.8≤a≤1, 0.3≤b≤0.9, 0≤c≤0.5, 0 <d≤0.33,-0.02≤e≤0.02; The organic acid is at least one of benzoic acid, acetic acid, citric acid, capric acid and tartaric acid.

2. The surface treatment method of an O3 type nickel-based sodium ion battery positive electrode material according to claim 1, characterized in that: The placing in organic acid, one specific scheme is: placing the O3 type nickel-based sodium ion battery positive electrode material in organic acid vapor, drying, and then sintering to obtain the surface treated positive electrode material.

3. The surface treatment method of a positive electrode material of an O3 type nickel-based sodium ion battery according to claim 2, characterized in that: The evaporation temperature of the organic acid is 100 to 1000° C., and the time of being placed in the organic acid vapor is 0.25 to 2 hours; The drying temperature is 60-150° C. and the drying time is 6-24 hours; The drying method is spray drying, blast drying or vacuum drying; 4. The surface treatment method of an O3 type nickel-based sodium ion battery positive electrode material according to claim 2, characterized in that: The sintering treatment is carried out in an atmosphere of air or oxygen, with a heating rate of 2 to 5°C / min, a sintering temperature of 850 to 1000°C, and a sintering time of 10 to 24 hours.

5. The surface treatment method of an O3 type nickel-based sodium ion battery positive electrode material according to claim 1, characterized in that: The method of placing the mixture in an organic acid is as follows: The O3 type nickel-based sodium ion battery positive electrode material is immersed in an organic acid solution, filtered, washed, dried, and then sintered to obtain a surface-treated positive electrode material.

6. The surface treatment method of an O3 type nickel-based sodium ion battery positive electrode material according to claim 5, characterized in that: The method of placing the mixture in an organic acid is as follows: The organic acid solution is prepared by dissolving the organic acid in pure water or ethanol solvent with a volume concentration of 10%-15%; The immersion time in the organic acid is 2-12 hours; The washing liquid is a neutral washing liquid.

7. The surface treatment method of an O3 type nickel-based sodium ion battery positive electrode material according to claim 5, characterized in that: The drying method is spray drying, air drying or vacuum drying; The drying temperature is 60-150° C. and the time is 6-24 hours.

8. The surface treatment method of an O3 type nickel-based sodium ion battery positive electrode material according to claim 5, characterized in that: The sintering treatment is carried out in an atmosphere of air or oxygen, with a heating rate of 2 to 5°C / min, a sintering temperature of 850 to 1000°C, and a sintering time of 10 to 24 hours.

9. An O3 type nickel-based sodium ion battery positive electrode material, characterized in that: Its surface is treated by any surface treatment method according to claims 1 to 8.

10. A battery, characterized in that: It comprises an O3 type nickel-based sodium ion battery positive electrode material obtained after surface treatment by any one of claims 1 to 8 or an O3 type nickel-based sodium ion battery positive electrode material according to claim 9.